Challenges and Limitation of Organic Farming - Abdusattorov B. A.; Sobirov B. B.; Qodirov S. Sh. (American Journal of Biology and Natural Sciences, 2024)
The global population is increasing at a rapid pace, posing significant challenges to sustainable development and food security. This review paper examines the advantages and challenges of organic farming as a potential solution to address the pressing issues in modern agriculture and food production. Organic farming offers a range of benefits, including improved soil fertility, higher profitability, reduced external input usage, land reclamation, improved market access, and enhanced farmer capacity and self-reliance. Organic farming practices prioritize environmental sustainability by reducing chemical usage and reliance on biological methods of pest control, as well as enhancing biodiversity, which strengthens ecological balance and resilience against pests and diseases. However, organic farming also faces challenges that need to be addressed for its widespread adoption. These challenges include uncertainty surrounding legislative environments, psychological and sociological costs of conversion, financial risks during the transition period, securing marketing channels for organic produce, and diminishing profit margins. Efforts should be made to provide farmers with the necessary support, including technical assistance, subsidies, and access to markets, to overcome these challenges. Despite the challenges, the potential of organic farming in promoting sustainable agriculture and ensuring a secure food system cannot be overlooked. It offers a natural and environmentally friendly approach to food production, prioritizing the health of both humans and the ecosystem.